Temperature-Dependent Transformation of Cells Infected with a Mutant of Bryan Rous Sarcoma Virus - Bader, John P. (1972)
Chick embryo cells infected with a mutant (Ta) of the Bryan high-titer strain of Rous sarcoma virus (RSV-BH) are morphologically transformed at 36 C but appear similar to uninfected cells at 41 C. When cells infected with RSV-BH-Ta are switched from 41 to 36 C, morphological changes characteristic of transformation are observable within 10 min. The transformation is reversible; cells shifted from 36 to 41 C have been observed to lose their transformed morphology within 1 hr. The transformation after a shift in temperature is unaffected by inhibition of deoxyribonucleic acid (DNA), ribonucleic acid (RNA), or protein synthesis, demonstrating that the proteins involved in the morphological change are already present. Transformed cells infected with RSV-BH or RSV-BH-Ta take up hexose and synthesize hyaluronic acid at higher rates than uninfected cells or RSV-BH-Ta-infected cells grown at 41 C. However, inhibition of either protein or RNA synthesis, but not DNA synthesis, prevented the induction of increased hexose uptake and hyaluronic acid synthesis after a shift of RSV-BH-Ta-infected cells from 41 to 36 C. Therefore, these biochemical changes are secondary to a more basic change responsible for morphological transformation.